Beyond The Reset: Forging a New Dynamic in U.S. – Russia Relations - Baunach, Leo; Campbell, Madison; Cohen, Mariella; Day, Erik; Deeny, Patrick; Erickson, Alexa; Fearey, Luke; Freedman, Samuel; Khalturina, Ksenia; MacDonald, Anna; Petrov, Konstantin; Price, Lauren; et al. (My University, 2013)
In the past decade the U.S. has seen its relationship with Russia slowly build and quickly deteriorate a number of times. A number of recent events exemplify this trend - Obama’s work with Medvedev building trust and cooperation, Putin’s reelection in 2012 and subsequent steps away from democracy, Russia’s retaliation against the Magnitsky Act banning U.S. adoptions of Russian children, and the recent dissolution of a joint working group dealing with security issues—and demonstrate the need for new strategic approaches to our relationship with Russia.
Volume 181: Beyond The Reset: Forging a New Dynamic in U.S. – Russia Relations
Created as part of the 2013 Jackson School for International Studies SIS 495: Task force. Scott Radnitz, Task Force Advisor; John Matlock, Evaluator; Konstantin Petrov, Coordinator.